(untitled) (JURNAL DURA NEGARA, 2026)
Indonesia, as a democratic country with cultural diversity, has strategic opportunities to utilize public diplomacy to strengthen its position at the global level. One concrete manifestation of this effort is the Tri Hita Karana Forum (THK Forum), initiated by the United in Diversity Foundation. The forum adopts Bali’s local wisdom, the concept of Tri Hita Karana, as its main conceptual framework, emphasizing harmonious relations between humans and god (parahyangan), humans and fellow human beings (pawongan), and humans and nature (palemahan). This research employs a qualitative approach with a descriptive-analytical method through the study of international policy documents and public diplomacy literature. The THK Forum has successfully become an international discussion space that facilitates cross-stakeholder collaboration through concrete initiatives such as the Global Blended Finance Alliance and the New Era Bali Kerthi Roadmap. The forum supports the mobilization of investment, sustainable financing innovation, and strategic cooperation in areas such as energy transition, nature conservation, regenerative agriculture, health, sustainable tourism, and the empowerment of local enterprises. The THK Forum constitutes an integral part of Indonesia’s public diplomacy framework.